Role of 18F-FDG PET/CT in patients affected by pulmonary primary lymphoma - Peng, Ying; Qi, Wanling; Luo, Zhehuang; Zeng, Qingyun; Huang, Yujuan; Wang, Yulu; Sharma, Amit; Schmidt-Wolf, Ingo G. H.; Liao, Fengxiang (Frontiers in Oncology, 2022)
BACKGROUND: Primary pulmonary lymphoma (PPL) is defined as clonal abnormal hyperplasia of lung parenchyma or bronchial lymphoid tissue. Owing to the lack of typical clinical symptoms and radiological features, it is challenging to accurately diagnose. Considering this, herein, we aim to raise awareness of this disease and help physicians understand the role of 18F-FDG PET/CT in the diagnosis of PPL. METHOD: A retrospective analysis was performed on the clinical and 18F-FDG PET/CT imaging data of 19 patients diagnosed with PPL by biopsy pathology at our hospital from April 2014 to December 2021. RESULTS: Among the 19 PPL patients, 15 patients showed clinical symptoms with the most common being fever and cough. In addition, there were 4 cases that had no clinical symptoms. In fact, 16 patients were misdiagnosed as lobar pneumonia, lung cancer, tuberculosis, and diffuse interstitial inflammation. 73.7% were MALT lymphomas, representing the most common pathological pattern. As to CT signs, the air-bronchial sign was found to be the most common, followed by the halo sign and the collapsed leaf sign. On the basis of the predominant radiologic features, lesions were categorized as pneumonic consolidation, nodular/mass type, diffuse interstitial type, and mixed type. The average SUVmax of lesions was 7.23±4.75. Of interest, the different pathological types of PPL showed different values of 18F-FDG uptake. The 18F-FDG uptake of DLCBL was the most prominent and was higher than that of MALT lymphoma. There appeared similarity in 18F-FDG uptake between MALT lymphoma and T-cell lymphoma. We found statistical significance between MALT lymphoma and DLCBL (P value<0.001). In addition, we also found statistical significance (P value < 0.05) in SUVmax of lesions between pneumonic consolidation type and nodal/mass type, Ⅰstage, and other stages. CONCLUSIONS: On 18F-FDG PET/CT images, certain features of PPL morphology and metabolism can be identified that may contribute to a better understanding of this disease. In addition, 18F-FDG PET/CT whole-body imaging has the potential to refine the staging of PPL. Importantly, functional 18F-FDG PET/CT imaging can readily reflect tumor cell activity, thus allowing for the selection of an optimal biopsy site. KEY WORDS: pulmonary primary lymphoma, 18F-FDG, PET/CT, Prospective